Challenges of liver transplantation programs in low‐ and middle‐income countries: An experience from Sri Lanka - M. J. S. Jayarathna; B. K. Dassanayake; Thinley Dorji; Don Eliseo Lucero‐Prisno III; S. Samarasinghe; Vasanthi Pinto; M. D. Lamawansa (Public Health Challenges)
Abstract Liver diseases lead to 1.3 million deaths per year around the world, the majority of which are secondary to cirrhosis. In the management of liver diseases in chronic and acute conditions, liver transplant (LT) plays a major role in improving the survival and quality of life of patients. LT programmes require the technical capabilities in performing the pre‐transplant evaluation, transplant surgery and post‐transplant care supported by adequate infrastructure and a set of trained teams. Globally, there were 28,000 deceased donor LTs, and 14,000 living donor LTs were performed in 2021. In the South Asia region, India, Pakistan and Sri Lanka conducted 2998 LTs in 2021. Many countries report sociocultural, religious and legislative barriers to acquiring adequate donor livers. We describe the challenges in LT programmes in low‐ and middle‐income countries and experiences from Sri Lanka. Sri Lanka carried out its first LT in 2010, and the service is provided free of charge in the state health sector. In Sri Lanka, the common indications for LT in adults are non‐alcoholic steatohepatitis, cirrhosis, hepatocellular carcinoma and alcoholic liver disease. In children, the indications are biliary atresia, hepatocellular carcinoma and Wilson disease. The common challenges include a lack of an adequate number of doctors and post‐transplant team members, a low number of organ donors and a long waiting list, all of which can be disadvantageous for transplant programmes. To continue providing LT services, there is a need to adopt multimodal strategies in the areas of providing additional skills training to the operating team and promoting organ donation culture in the background of supportive organ donation legislation. With the adoption of the national strategic plan for organ, tissue and cell transplantation, the country hopes to strengthen its capacity of providing transplant services to its people.